Maori Television. - Smith, Jo (Auckland University Press, 2016)
"Based on a Marsden Grant and three years of interviews with key stakeholders, this is a deep account of Māori Television in its first ten years. Jo Smith argues that today's arguments must be understood within a broader context shaped by non-Māori interests. Can a Māori broadcaster follow both tikanga and the Broadcasting Standards Authority? Is it simply telling the news in Māori, or broadcasting the news with a Māori perspective? How can it support te reo Māori at the same time as appeal to all New Zealand? How does it function as the voice of its Māori stakeholders?"--Publisher information.